Additive anti-inflammatory effect of formoterol and budesonide on human lung fibroblasts. Issue 3 (1st March 2002) - Spoelstra, F M; Postma, D S; Hovenga, H; Noordhoek, J A; Kauffman, H F
Abstract : Background: It has been shown that treatment with a long acting β2 agonist in addition to a glucocorticoid is beneficial in the treatment of asthma. In asthma inflammatory cells, particularly eosinophils, migrate into the pulmonary tissue and airway lumen by means of adhesion molecules expressed on resident tissue cells—that is, fibroblasts—and become activated by cytokines and adhesive interactions. A study was undertaken to determine whether an interaction exists between the long acting β2 agonist formoterol and the glucocorticoid budesonide on inhibition of adhesion molecule expression, as well as chemo/cytokine production by human lung fibroblasts. Methods: Lung fibroblasts were preincubated with therapeutically relevant drug concentrations of 10 −8 M to 10 −10 M. Cells were stimulated with interleukin (IL)-1β (1 or 10 U/ml) for 8 hours and supernatants were collected for measurement of GM-CSF and IL-8 concentrations. The cells were fixed and subjected to a cell surface ELISA technique to measure the expression of ICAM-1 and VCAM-1. Results: Formoterol exerted an additive effect on the inhibition of IL-1β stimulated ICAM-1 and VCAM-1 upregulation and GM-CSF production by budesonide in concentrations of 10 −9 M and above (p<0.05). IL-8 production was not influenced by formoterol. Conclusion: Formoterol exerts an additive effect on the anti-inflammatory properties of budesonide. In vitro data support the finding that the combination of budesonide and formoterol in asthma treatment strengthens the beneficial effect of either drug alone.